Early features of pancreatic cancer on magnetic resonance imaging (MRI): a case–control study. - Parker, Rex A.; Zhou, Yichen; Puttock, Eric J.; Chen, Wansu; Lustigova, Eva; Wu, Bechien U. (Abdominal Radiology, 2024)
Purpose: Magnetic resonance imaging has been recommended as a primary imaging modality among high-risk individuals undergoing screening for pancreatic cancer. We aimed to delineate potential precursor lesions for pancreatic cancer on MR imaging. Methods: We conducted a case–control study at Kaiser Permanente Southern California (2008–2018) among patients that developed pancreatic cancer who had pre-diagnostic MRI examinations obtained 2–36 months prior to cancer diagnosis (cases) matched 1:2 by age, gender, race/ethnicity, contrast status and year of scan (controls). Patients with history of acute/chronic pancreatitis or prior pancreatic surgery were excluded. Images underwent blind review with assessment of a priori defined series of parenchymal and ductal features. We performed logistic regression to assess the associations between individual factors and pancreatic cancer. We further assessed the interaction among features as well as performed a sensitivity analysis stratifying based on specific time-windows (2–3 months, 4–12 months, 13–36 months prior to cancer diagnosis). Results: We identified 141 cases (37.9% stage I-II, 2.1% III, 31.4% IV, 28.6% unknown) and 292 matched controls. A solid mass was noted in 24 (17%) of the pre-diagnostic MRI scans. Compared to controls, pre-diagnostic images from cancer cases more frequently exhibited the following ductal findings: main duct dilatation (51.4% vs 14.3%, OR [95% CI]: 7.75 [4.19–15.44], focal pancreatic duct stricture with distal (upstream) dilatation (43.6% vs 5.6%, OR 12.71 [6.02–30.89], irregularity (42.1% vs 6.0%, OR 9.73 [4.91–21.43]), focal pancreatic side branch dilation (13.6% vs1.6%, OR 11.57 [3.38–61.32]) as well as parenchymal features: atrophy (57.9% vs 27.4%, OR 46.4 [2.71–8.28], focal area of signal abnormality (39.3% vs 4.8%, OR 15.69 [6.72–44,78]), all p < 0.001). Conclusion: In addition to potential missed lesions, we have identified a series of ductal and parenchymal features on MRI that are associated with increased odds of developing pancreatic cancer.